Konsumerisme Dan Krisis Lingkungan: Tinjauan Kritis Pendidikan dan Spiritualitas Ekologis dalam Ensiklik Laudato Si Paus Fransiskus - Sugar, Felix Riondi (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This paper discusses the concept of ‘Ecological Education and Spirituality’ introduced by Pope Francis in his encyclical Luadato Si and its relevance in criticising consumerism in today's world. The development of consumerism in people's lives has been accused of being one of the causes of the environmental crisis, particularly in terms of waste. Therefore, the purpose of writing this article is to remind and correct the pattern of excessive consumerism in modern times based on the perspective of Pope Francis in the encyclical Laudato Si. To elaborate on all of this, the author uses a qualitative research method with literature review as a way to collect data and focuses on document studies. Thus, the material object of this research is consumerism, while the formal object is Pope Francis' perspective in the encyclical Laudato Si. From the study, the author found results that show the relationship between consumerism and life style, the use of social media and gadgets that contribute to changing the socio-economic psychology of society, and the influence of consumerism on the increasing population of waste. In addition, this article focuses on how the concept of ‘Ecological Education and Spirituality’ in Luadato Si can serve as a framework for changing consumptive worldviews, and also offers practical insights that can be adopted in the development of more inclusive and sustainable environmental policies in this modern era.